Access to care and factors that impact access, patients as partners in care and changing roles of health providers - Kronenfeld, Jennie J. (Emerald, 2011)
This volume in the highly-regarded Research in the Sociology of Health Care series, deals with both macro-level system issues and micro-level issues involving access to care, factors that impact access, patients as partners in care and changing roles of health providers. It includes: examination of factors that impact access to care such as racial/ethnic, social, demographic and structural sources, discussion of changing patterns of care and changing patterns of interaction between patients and providers of care, and investigation of changing roles of health care providers within the health care delivery system. Key contributions focus on linkages to policy, population concerns and patients and/or providers of care as ways to meet health care needs of people both in the US and in other countries. This volume relates to issues of consumers of health care services, providers of such services and policy perspectives. It also raises issues of the availability of services, access to those services, quality of services and the role of government in services provision.
Keywords: Health services accessibility.; Medical policy.; Health & Fitness -- Health Care Issues.; Social Science -- Sociology -- General.; Medical -- Health Care Delivery.; Health systems & services.; Sociology.; elektronické knihy; electronic books